2016
DOI: 10.1159/000445866
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Value Is the Most Important Factor in the Development of Hand-Foot Syndrome under the Capecitabine Regimen

Abstract: Background: Hand-foot syndrome (HFS) is a common side effect that has a high occurrence rate with capecitabine (Cape) chemotherapy. However, little is known about the risk factors of developing HFS under the Cape regimen. Our aim was to examine these risk factors. Methods: A univariate analysis was used to determine the risk factors associated with developing HFS, and we calculated the effect sizes between the patients who developed HFS compared to those who did not. Results: Of the 52 patients enrolled in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…A total of 2081 patients (mean sample size: 122; median sample size with corresponding range: 106 ) were included in this meta-analysis. 11,27 The following prevention strategies were addressed in the analyzed studies: pyridoxine (10 studies) 8,11,12,[19][20][21][22]24,26,27 ; topical urea/ lactic acid (three studies) 8,10,25 ; celecoxib (two studies) 9,28 ; and moisturizing cream, topical silymarin, Fuzheng Jiedusan and neurotropin (four studies). 8,17,19,27,28 Fifteen studies only assessed the prophylactic efficacies of prevention strategies, [8][9][10][11][12][17][18][19][20][21][22][23][24][25][26][27][28] and two studies assessed prophylactic and treatment efficacies.…”
Section: What's New?mentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 2081 patients (mean sample size: 122; median sample size with corresponding range: 106 ) were included in this meta-analysis. 11,27 The following prevention strategies were addressed in the analyzed studies: pyridoxine (10 studies) 8,11,12,[19][20][21][22]24,26,27 ; topical urea/ lactic acid (three studies) 8,10,25 ; celecoxib (two studies) 9,28 ; and moisturizing cream, topical silymarin, Fuzheng Jiedusan and neurotropin (four studies). 8,17,19,27,28 Fifteen studies only assessed the prophylactic efficacies of prevention strategies, [8][9][10][11][12][17][18][19][20][21][22][23][24][25][26][27][28] and two studies assessed prophylactic and treatment efficacies.…”
Section: What's New?mentioning
confidence: 99%
“…Of the eligible studies, 12 were RCTs, [9][10][11][12]18,[20][21][22][23][24][25][26] and five were cohort studies. [17][18][19]23 The main characteristics of the included studies are shown in Table 1. 11,27 The following prevention strategies were addressed in the analyzed studies: pyridoxine (10 studies) 8,11,12,[19][20][21][22]24,26,27 ; topical urea/ lactic acid (three studies) 8,10,25 ; celecoxib (two studies) 9,28 ; and moisturizing cream, topical silymarin, Fuzheng Jiedusan and neurotropin (four studies).…”
Section: What's New?mentioning
confidence: 99%
See 3 more Smart Citations